The Janus Kinase (JAK) FERM and SH2 Domains: Bringing Specificity to JAK–Receptor Interactions - Ferrao, Ryan; Lupardus, Patrick J. (Frontiers in Endocrinology, 2017)
The Janus kinases (JAKs) are non-receptor tyrosine kinases essential for signaling in response to cytokines and interferons and thereby control many essential functions in growth, development, and immune regulation. JAKs are unique among tyrosine kinases for their constitutive yet non-covalent association with class I and II cytokine receptors, which upon cytokine binding bring together two JAKs to create an active signaling complex. JAK association with cytokine receptors is facilitated by N-terminal FERM and SH2 domains, both of which are classical mediators of peptide interactions. Together, the JAK FERM and SH2 domains mediate a bipartite interaction with two distinct receptor peptide motifs, the proline-rich “Box1” and hydrophobic “Box2,” which are present in the intracellular domain of cytokine receptors. While the general sidechain chemistry of Box1 and Box2 peptides is conserved between receptors, they share very weak primary sequence homology, making it impossible to posit why certain JAKs preferentially interact with and signal through specific subsets of cytokine receptors. Here, we review the structure and function of the JAK FERM and SH2 domains in light of several recent studies that reveal their atomic structure and elucidate interaction mechanisms with both the Box1 and Box2 receptor motifs. These crystal structures demonstrate how evolution has repurposed the JAK FERM and SH2 domains into a receptor-binding module that facilitates interactions with multiple receptors possessing diverse primary sequences.